Depressive Symptoms, Leisure Activity Engagement, and Global Cognition in Non-Hispanic Black and White Older Adults. (13th August 2021) - Sharifian, Neika; Sol, Ketlyne; Zaheed, Afsara B; Morris, Emily P; Palms, Jordan D; Martino, Alexa G; Zahodne, Laura B
Abstract: Objectives: Prior research indicates that depressive symptoms disproportionately affect cognition in non-Hispanic Blacks relative to non-Hispanic Whites. Depressive symptoms have been linked to worse global cognition in older adulthood through lower leisure activity engagement, but less is known regarding the distinct types of activities that drive these associations and whether associations involving depressive symptoms, leisure activities, and cognition differ across racial groups. Methods: This cross-sectional study used data from the Michigan Cognitive Aging Project ( n = 453, 52.80% Black, M age = 63.60 years). Principal components analysis identified 6 subtypes of leisure activities (cognitive, creative, community, physical, children, and games). Mediation models examined whether distinct leisure activity subtypes mediated the association between depressive symptoms and performance on a comprehensive neuropsychological battery and whether race moderated these associations. Results: There were no racial differences in the level of depressive symptoms after adjusting for sociodemographic, socioeconomic, and health covariates. Only lower cognitive activity engagement mediated the negative association between depressive symptoms and global cognition. Multigroup models revealed that this indirect effect was only evident in Blacks, who showed a stronger negative association between depressive symptoms and cognitive activity engagement than Whites. After accounting for indirect effects, a direct effect of higher depressive symptoms on worse cognition remained and did not differ across racial groups. Discussion: Depressive symptoms may disproportionately affect cognition among Blacks through a greater negative impact on engagement in cognitively stimulating activities that have been shown to promote cognitive reserve. Additional research is necessary to identify other mechanisms linking depressive symptoms and cognition.